Proposed Role for KaiC-Like ATPases as Major Signal Transduction Hubs in Archaea - Kira S. Makarova (American Society for Microbiology, 2017)
ABSTRACT All organisms must adapt to ever-changing environmental conditions and accordingly have evolved diverse signal transduction systems. In bacteria, the most abundant networks are built around the two-component signal transduction systems that include histidine kinases and receiver domains. In contrast, eukaryotic signal transduction is dominated by serine/threonine/tyrosine protein kinases. Both of these systems are also found in archaea, but they are not as common and diversified as their bacterial and eukaryotic counterparts, suggesting the possibility that archaea have evolved other, still uncharacterized signal transduction networks. Here we propose a role for KaiC family ATPases, known to be key components of the circadian clock in cyanobacteria, in archaeal signal transduction. The KaiC family is notably expanded in most archaeal genomes, and although most of these ATPases remain poorly characterized, members of the KaiC family have been shown to control archaellum assembly and have been found to be a stable component of the gas vesicle system in Halobacteria. Computational analyses described here suggest that KaiC-like ATPases and their homologues with inactivated ATPase domains are involved in many other archaeal signal transduction pathways and comprise major hubs of complex regulatory networks. We predict numerous input and output domains that are linked to KaiC-like proteins, including putative homologues of eukaryotic DEATH domains that could function as adapters in archaeal signaling networks. We further address the relationships of the archaeal family of KaiC homologues to the bona fide KaiC of cyanobacteria and implications for the existence of a KaiC-based circadian clock apparatus in archaea. IMPORTANCE Little is currently known about signal transduction pathways in Archaea. Recent studies indicate that KaiC-like ATPases, known as key components of the circadian clock apparatus in cyanobacteria, are involved in the regulation of archaellum assembly and, likely, type IV pili and the gas vesicle system in Archaea. We performed comprehensive comparative genomic analyses of the KaiC family. A vast protein interaction network was revealed, with KaiC family proteins as hubs for numerous input and output components, many of which are shared with two-component signal transduction systems. Putative KaiC-based signal transduction systems are predicted to regulate the activities of membrane-associated complexes and individual proteins, such as signal recognition particle and membrane transporters, and also could be important for oxidative stress response regulation. KaiC-centered signal transduction networks are predicted to play major roles in archaeal physiology, and this work is expected to stimulate their experimental characterization.